RUANG BERNORMA PADA HIMPUNAN SEMUA FUNGSI TERDEKATI - Abdul Aziz; Y.D. Sumanto; Solikhin Solikhin; Robertus Heri Soelistyo Utomo (Journal of Fundamental Mathematics and Applications (JFMA), 2019)
In this paper, we discuss that in the approachable functions set can be defined a complete norm. Furthermore, we obtained that all of approachable functions set is a Banach Space.